New media: future dimensions in sport marketing - Santomier, J.; Shuart, J. (Pre-olympic Congress 2004. Thessaloniki, Grécia. de 6 a 11 de Agosto de 2004, 2004)
Introduction The term New Media describes any digital media production that is interactive and digitally distributed. Two fundamental points that distinguish new media from media that preceded it are: 1) how it is transmitted and accessed (emphasis on the integration of text, pictures, video, sound; and the increasing use of the Internet); and 2) interactivity. The purposes of this presentation are to: 1) examine the direct affect of new media technologies on the future of the sport industry; 2) identify the key factors and unique problems related to sport marketing and new media; and 3) present new business models, revenue streams, and new licensing opportunities related to new media. Methods A meta-analysis of salient research related to new media in sport was conducted, and recurring themes and concepts were developed and further investigated. Information was also gathered via interviews with new media and sport executives. Secondary sources of information included trend analyses, technical reports, and U.S. Department of Commerce Reports. Results The relationship among sports governing bodies, franchises, leagues, broadcasters, marketing and technology companies, traditional media, athletes and fans will be significantly and dramatically changed in the future. Results indicated that the sport broadcast environment is undergoing dynamic restructuring and this fundamental shift in the balance of power will drastically reduce the influence that television networks have over sport. Discussion / Conclusions Integration of new technologies, specifically broadband, wireless, digital and interactive TV (iTV), High Definition TV, and Internet platforms, have allowed sport fans to select events from anywhere in the world, choose how and when they want to watch, compare live action to archive footage, call down any amount of information, or buy licensed merchandise. A key point is that new media platforms have blurred traditional sport industry roles. Broadcasters as team owners, governing bodies as broadcasters, and online networks as commercial partners are just some of the resulting permutations. Probably the most significant opportunity for sport presented by New Media is its ability to develop a deeper relationship with fans.